Scaling of the process of biosynthesis of surfactants by Rhodococcus erythropolis ek-1 on hexadecane - Pirog, Tatiana; Ignatenko, Sergey (My University, 2011)
Peculiarities of synthesis of surface-active substances (SAS) are studied at periodical cultivation of Rhodococcus erythropolis EK-1 in the AK-210 fermenter on medium containing n-hexadecane. Maximum indicators of SAS synthesis (concentration of extra cellular SAS is 7.2 g/l; factor of emulsification of the cultural liquid 50%; SAS yield from the substrate 50%) have been observed at 60–70% concentration of dissolved oxygen from the saturation level with aerial oxygen (pH 8.0) fractional supply of the substrate by portions each being 0.3–0.4% every 5–6 h to a final volume concentration of 2.4% and with the use of 10% inoculate grown until mid-exponential phase on the medium with 1.0 vol % of n-hexadecane. Implementation of the process of SAS biosynthesis with the fermentation equipment provided the possibility to increase almost two-fold the amount of the synthesized SAS and reduce 3.5-fold the time of cultivation of the producer strain compared with the growth in flasks at shake-flask propagator.
Keywords: surfactants; Rhodococcus erythropolis ЕК-1; hexadecane; scaling; biosynthesis; поверхнево-активні речовини; гексадекан; масштабування; біосинтез; кафедра біотехнології і мікробіології